1985
DOI: 10.1002/jat.2550050503
|View full text |Cite
|
Sign up to set email alerts
|

Excretion of 3‐hydroxy‐benzo(a)pyrene and mutagenicity in rat urine after exposure to benzo(a)pyrene

Abstract: 3-hydroxy-benzo(a)pyrene (3-OH-B(a)P) and mutagenic activity in rat urine were determined after the oral administration of benzo(a)pyrene given in three repeated doses of 10, 20 and 50 mumol kg-1. The procedure for the determination of 3-OH-B(a)P consisted of enzymic hydrolysis, separation and HPLC-analysis. The mutagenic activity of concentrated urine samples was assayed with the Salmonella typhimurium strain TA98 in the presence of S9 mix and beta-glucuronidase. The urinary excretion of 3-OH-B(a)P and mutage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
1

Year Published

1986
1986
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 9 publications
1
10
1
Order By: Relevance
“…However, our results (0.20-0.49% of BaP dose excreted as urinary 3-OHBaP) are somewhat similar to those obtained by Jongeneelen et al (1985), who reported 0.22-0.35% of BaP dose excreted in urine as 3-OHBaP during 6 days following 3 consecutive days of oral treatment of rats with BaP alone at doses of about 2.4, 5 and 12 mg/kg, calculated on the basis of the last given dose. It has to be kept in mind that the exposure route, duration of exposure, exposure doses and urine collection period, as well as diet, differed in both studies.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, our results (0.20-0.49% of BaP dose excreted as urinary 3-OHBaP) are somewhat similar to those obtained by Jongeneelen et al (1985), who reported 0.22-0.35% of BaP dose excreted in urine as 3-OHBaP during 6 days following 3 consecutive days of oral treatment of rats with BaP alone at doses of about 2.4, 5 and 12 mg/kg, calculated on the basis of the last given dose. It has to be kept in mind that the exposure route, duration of exposure, exposure doses and urine collection period, as well as diet, differed in both studies.…”
Section: Discussionsupporting
confidence: 93%
“…It has to be kept in mind that the exposure route, duration of exposure, exposure doses and urine collection period, as well as diet, differed in both studies. Our results did not confirm the findings of Jongeneelen et al (1985) that the lower the BaP exposure dose the higher is the percentage of BaP dose excreted in urine as 3-OHBaP. However, it is well known that repeated exposure of rats to BaP may trigger induction of the cytochrome P450 enzyme system.…”
Section: Discussioncontrasting
confidence: 80%
“…PAHs and their metabolites can be measured in the urine of exposed individuals. In workers exposed to PAHs and dermatology patients treated with coal tar, the PAH metabolite 1-hydroxypyrene has been detected in the urine at concentrations of 0-40 µg/g creatinine or 290 ng/g creatinine, respectively (Jongeneelen et al 1985). The amount of 1-hydroxypyrene detected in urine samples taken during the weekend was less than that detected during the weekdays, when the exposure was presumably higher than on the weekends.…”
Section: Health Effectsmentioning
confidence: 90%
“…17 ' 86^90 Methods were then developed to directly determine the concentration of excreted PAH metabolites in the urine. Compared to any extrapolations from working place ambient air measurements, determination of the urinary metabolites provides a much better estimate of the actual overall systemic dose of PAHs incorporated by a single person.…”
Section: Principal Considerationsmentioning
confidence: 99%